DIRECTORS' LIABILITY FOR UNLAWFUL DIVIDENDS - Ferran, Eilís (Cambridge law journal, 2011)
Companies can pay dividends only out of profits available for distribution. The amount for distribution must be justified by reference to the company's "relevant accounts", usually its last annual accounts. If a problem with those accounts emerges later, what is the position of the directors who authorised the payment of dividends in reliance on those accounts? Are they strictly liable to make good the amounts that were paid out to the shareholders, subject to the possibility of the court granting relief under section 1157 of the Companies Act 2006? Or does the liability of the directors depend on "fault"? Either way, the end position for the honest and careful director may be that she does not have to make good the amounts paid away but the route by which that conclusion is arrived at still matters. For a director who cares about her reputation, a finding that she was not in breach of duty at all is likely to be preferable to exoneration only through the court's exercise of a "prerogative of mercy" in respect of a technical or otherwise forgivable breach. Moreover, when she learns that there are relatively few reported cases in which directors have succeeded in claiming this relief, the prudent director is very likely to conclude that this possibility offers only limited practical reassurance.